2009
DOI: 10.1111/j.1651-2227.2009.01238.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐differences in Apgar scores for full‐term neonates

Abstract: of the vena cava, and impaired venous return. This situation can be easily resolved by insertion of a venous cannula into the abdomen [2][3]. One should avoid the right upper quadrant in performing this procedure as the large neonatal liver can be injured. Cannula decompression of a tension pneumoperitoneum is a technique which can be performed as a life-saving measure by neonatologists, paediatricians and nursing staff involved in the care and transfer of neonates. Further reading 1. Rampton JW. The football … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
(13 reference statements)
3
8
1
Order By: Relevance
“…Similar findings were also reported reported by the study done El-Auoty M et al and other studies. [11][12][13] In present study the average gestational age is 40 weeks which is similar to studies reported by El-Auoty M et al and various other studies. 11,12,14 In study reported Allemand F et al the average gestational age is 35 weeks the difference is because they also included preterm neonates in their study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar findings were also reported reported by the study done El-Auoty M et al and other studies. [11][12][13] In present study the average gestational age is 40 weeks which is similar to studies reported by El-Auoty M et al and various other studies. 11,12,14 In study reported Allemand F et al the average gestational age is 35 weeks the difference is because they also included preterm neonates in their study.…”
Section: Discussionsupporting
confidence: 90%
“…In studies reported by, El Auoty M et al the percentage of normal EEG is less when compared to present study findings which is due to difference in study inclusion criteria as in their study most of patients had severe perinatal asphyxia. 11,13,14 In present study the classification of perinatal asphyxia is based on APGAR score. 30% mild,65% moderate and 5% had severe perinatal asphyxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predisposition for preterm delivery in male gestations has been implied it the low Apgar score that neonatal boys present. However, this phenomenon has been shown even when preterm boys are compared with preterm girls [41]. In our study neither birth weight nor newborn gender was associated with low Apgar score.…”
Section: Cocontrasting
confidence: 79%
“…Also, Islami and Fallah (2008) suggested that Apgar score was no related to gender. But Kaveh et al (2004) and Nagy et al (2009) reported a significant relation between Apgar score and gender.…”
Section: Discussionmentioning
confidence: 99%